Protective mitochondrial fission induced by stress-responsive protein GJA1-20k - Daisuke Shimura (eLife Sciences Publications Ltd, 2021)
The Connexin43 gap junction gene GJA1 has one coding exon, but its mRNA undergoes internal translation to generate N-terminal truncated isoforms of Connexin43 with the predominant isoform being only 20 kDa in size (GJA1-20k). Endogenous GJA1-20k protein is not membrane bound and has been found to increase in response to ischemic stress, localize to mitochondria, and mimic ischemic preconditioning protection in the heart. However, it is not known how GJA1-20k benefits mitochondria to provide this protection. Here, using human cells and mice, we identify that GJA1-20k polymerizes actin around mitochondria which induces focal constriction sites. Mitochondrial fission events occur within about 45 s of GJA1-20k recruitment of actin. Interestingly, GJA1-20k mediated fission is independent of canonical Dynamin-Related Protein 1 (DRP1). We find that GJA1-20k-induced smaller mitochondria have decreased reactive oxygen species (ROS) generation and, in hearts, provide potent protection against ischemia-reperfusion injury. The results indicate that stress responsive internally translated GJA1-20k stabilizes polymerized actin filaments to stimulate non-canonical mitochondrial fission which limits ischemic-reperfusion induced myocardial infarction.